Analysis of The Role of Youth Workers in Fishery Sector : Case Study in Lamongan, East Java - Anam, M. Khairul; Prihatini, Endah Sih; Mas’ud, Faisol (Sangia Research Media and Publishing, 2021)
This study aims to examine the dynamics of the labor in the fisheries sector in Lamongan Regency. Factors influencing youth labor interest in the fisheries sector, and formulating policies to attract youth to work in the fisheries sector. The analytical method used is logit regression analysis. The results of this study indicated that the variable that has a significant effect on youth's decision to be involved in the fisheries sector or not is the non-fishing income variable. Where if non-fishery income is above the city/district minimum wage, respondents will tend to choose to work outside of fisheries, and vice versa. In order to attract youth workers to work in the fisheries sector, the thing that can be done is to make the results obtained from this field beyond other fields. Therefore, one thing that policy makers can do is about determining the price of fishery output and input, because these two variables are beyond the control of farmers. So, with high output prices and low input prices, the income of farmers in the fisheries sector will be higher and it is hoped that it will attract young workers to choose this sector.